Patterns of regional firm mobility in Germany - Benedikt Schröpf; Tim Kovalenko (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2024)
Although domestic establishment relocations are part of both the factor reallocation across regions and establishment dynamics within an economy, evidence on firm mobility in Germany is rather scarce. In this study, we therefore examine establishment- and regional-level patterns of firm mobility in Germany. Using rich administrative data, we document that most relocation flows go from major cities to the surrounding urban districts, suggesting sub-urbanization patterns. In terms of establishment-level characteristics, we document that middle-sized and knowledge-intensive establishments exhibit high relocation propensities. Further, establishments moving to major cities or urban districts are rather high-wage establishments while establishments moving to rural districts are rather low-wage establishments. Our regional analyses reveal that relocating establishments prefer nearby regions with (compared to their old locations) low tax burdens and low population densities.
Keywords: R10; R12; R30; 330; Firm mobility; Establishment Relocation; Firm Location; Germany